Photothermal-assisted cleaning and reusability of MXene-MWCNT membranes for efficient oil–water separation - Siyoung Byun; Dongjin Sim; Alicia Kyoungjin An; Eui-jong Lee; Jae-Wuk Koo; Tae-Mun Hwang; Sanghyun Jeong (npj Clean Water)
Abstract Membrane-based separation can efficiently treat oily wastewater; however, the trade-off between flux and oil rejection, as well as susceptibility to oil fouling, particularly when dealing with highly viscous oils, often limits its applicability. To address these limitations, MXene-multi-walled carbon nanotube (MWCNT) composite membranes were fabricated, exhibiting improved permeate flux and anti-fouling performance. The fabricated MXene-MWCNT membrane showed an oil emulsion permeate flux exceeding 19 L/m²∙h (LMH), along with a high oil rejection efficiency (~95%), effectively mitigating the conventional trade-offs associated with membrane-based separations. However, the membrane was susceptible to irreversible oil fouling when exposed to highly viscous oils, thus challenging sustainable operation. To overcome this issue, a photothermal-assisted cleaning strategy was employed. This approach enhances localized photothermal heating to reduce fouling and enhance membrane reusability. The MXene-MWCNT membrane maintained an adequate flux recovery rate (>60%) and a stable oil rejection efficiency (~99%) over four operational cycles. In comparison, membranes without photothermal cleaning achieved a flux recovery of only ~7% under similar conditions. Given its high permeate flux, excellent oil rejection performance, and enhanced anti-fouling properties achieved via photothermal-assisted cleaning, the MXene-MWCNT membrane offers a sustainable and effective solution for practical oil–water separation applications, particularly when treating wastewater containing highly viscous oils.